DETERMINING THE MODERATING EFFECT OF ENVIRONMENT ON THE BUSINESS STRATEGY-PERFORMANCE RELATIONSHIP IN MALAYSIAN SMES - hashim, Mohd khairuddin; Wafa, Syet Azizi; sulaiman, mohamed (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
Previous research that examined environment as a moderator between business strategy performance linkage has mainly focused on large firms. Little reserch exists that investigate this relationship in small and medium-sized enterprises (SMEs). This study empirically examines environment as the moderator of the relationship between business strategy and performance of 100 SMEs in the malaysia manufacturing sector. The findings of this study suggest that not onlydoes the prformance of Sme vary with the coice of the business strategy they adopted, but the relationship between business strstegy and the performance of SMEs is moderated by by the environment